Estudo teórico-experimental do dano em vigas de concreto - Carvalho, Pedro Paulo Martins de (2015)
The need for damage conditions detection in concrete beams is becoming more important. Especially when it concerns the goal of obtaining structures with greater durability and ease of maintenance. In this context, it inserts the need to develop methods for the evaluation of this damage conditions in beams. The objective of his work is to study damage detection methods beams initially through a dynamic analysis and then with greater emphasis on static response in terms of rigidity of the beams. These approaches are applied to the beam in damage conditions and in the healthy state of reference. This work consists essentially of an experimental analysis, consisting of tests of concrete beams, and a statistical analysis to determine differences between the damaged condition and the full condition of the beams. The work of experimental analysis involves subjecting beams in flexural strength and evaluate the static response in order to detect signs of damage. It was initially applied a dynamic analysis tested for flexural beams by means of Fourier transform applied to an acceleration signal in the time domain. However, for this study, results showed that such an approach has not led to the formulation parameters for the detection of damage. Thus, the main work approach consisted in detecting damage from the application of the static response in terms of stiffness of the flexure beams tested. Studies for the states before and after the break and the full and damaged beams of conditions are fulfilled. From a statistical study of the results obtained, it was possible to distinguish the undamaged and damaged states in the tested beams.